1990
DOI: 10.1177/014107689008300806
|View full text |Cite
|
Sign up to set email alerts
|

Skin Damage in Chronic Venous Insufficiency: Does an Oxygen Diffusion Barrier Really Exist?

Abstract: Eleven patients with lipodermatosclerosis (LDS) and 14 patients without venous or arterial disease underwent measurement of xenon-133 (133Xe) half-clearance times from the gaiter region of the leg. Xenon has similar diffusion characteristics to oxygen, and the investigation reflects the ability of the isotope to diffuse from the skin surface into capillary blood. Median skin half-clearance time for skin in the LDS group was 2.2 min and in the control group 2.1 min. From the subcutaneous tissues, the respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Therefore, they argued that the fibrin cuff creates an exchange barrier that inhibits adequate diffusion of oxygen and nutrients, leading to a state of tissue deficit that impairs proper wound healing. However, in 1990, Cheatle et al (1990) questioned this idea of an impermeable barrier in their study that failed to demonstrate decreased permeability of 133 Xenon, a molecule with diffusion characteristics similar to those of oxygen. They argued that the fibrin cuff that is deposited around the capillary bed was probably of different composition than the 1-mm fibrin used, as it was manufactured by a commercial surgical suture manufacturer for tissue repair procedures.…”
Section: ''Fibrin Cuff'' Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they argued that the fibrin cuff creates an exchange barrier that inhibits adequate diffusion of oxygen and nutrients, leading to a state of tissue deficit that impairs proper wound healing. However, in 1990, Cheatle et al (1990) questioned this idea of an impermeable barrier in their study that failed to demonstrate decreased permeability of 133 Xenon, a molecule with diffusion characteristics similar to those of oxygen. They argued that the fibrin cuff that is deposited around the capillary bed was probably of different composition than the 1-mm fibrin used, as it was manufactured by a commercial surgical suture manufacturer for tissue repair procedures.…”
Section: ''Fibrin Cuff'' Theorymentioning
confidence: 99%
“…Duplex ultrasound, the gold standard in diagnosing venous reflux, was used in only half of the studies. Finally, of the 18 observational or interventional studies, 15 did not exclude patients with diabetes (Burnand et al, 1982a, b;Coleridge Smith et al, 1988;Thomas et al, 1988;Cheatle et al, 1990;Trengove et al, 1996;Weyl et al, 1996;Loots et al, 1998;Takase et al, 1999;Danielsson et al, 2003) or infection (Burnand et al, 1982a, b;Coleridge Smith et al, 1988;Thomas et al, 1988;Layton et al, 1994;Trengove et al, 1996;Weyl et al, 1996;Loots et al, 1998;Takase et al, 1999;Abd-El-Aleem et al, 2005). Given the effects of diabetes and infection on chronic inflammation, it is difficult to clearly identify the role of inflammatory cells in chronic venous disease.…”
Section: Inflammatory Cell ''Trap'' Theorymentioning
confidence: 99%
“…However, factors other than a low oxygen delivery have to be involved in the pathogenesis of venous leg ulcers [69]. Theoretical calculations [70] and some clinical studies also challenge the concept of a reduced oxygen transport to the cells as the major cause of venous leg ulcers, and suggest instead that this might be nondelivery of other nutritional substances or the toxic effects of elements released from, for example, white cells trapped in the region [71,72]. However, an improvement in tcP # values has been reported after intermittent compression treatment of venous ulcers ; this indicates improved oxygenation of the tissue, which supports the concept that oxygen transportation to the skin cells is disturbed in chronic venous insufficiency [61,73].…”
Section: Chronic Venous Insufficiencymentioning
confidence: 99%
“…A protein-rich interstitial edema ensues when lymphatic drainage is overwhelmed. However, since Cheatle et al have demonstrated that oxygen diffusion is not disturbed in patients with venous insufficiency, the validity of the fibrin cuff theory is uncertain [14]. It is unclear whether the increased fibrinogen filtration supplies the matrix for enhanced subendothelial collagen deposition or whether the elevated venous pressure stimulates the endothelial cells to produce surplus collagen [12.13], Burnand et al have suggested that the perivascular fibrin cuffs interfere with passage of oxygen and nutrients to the tissues.…”
Section: Subcutaneous Microangiopathymentioning
confidence: 99%